Preparation and characterization of simvastatin/DMβCD complex and its pharmacokinetics in rats - Gu Fugen; Ning Jia; Fan Huimin; Wu Chunzhi; Wang Yi (Acta Pharmaceutica)
Simvastatin is poorly bioavailable because it is practically insoluble in water and shows dissolution rate-limited absorption. Solubilizing effects of several β-cyclodextrin (βCD) derivatives such as HPβCD, SBEβCD and DMβCD on simvastatin in aqueous solution were investigated using the phase solubility technique. The solubility diagram of simvastatin with each βCD derivative could be classified as AL-type, indicating soluble complex formation of 1:1 stoichiometry. Among the above βCD derivatives DMβCD was found to be the ideal complexing agent for improving drug solubility. The simvastatin complex with DMβCD was prepared using the co-evaporation method and was then characterized by differential scanning calorimetry (DSC), Fourier-transform infrared spectroscopy (FT-IR) and in vitro dissolution. Dissolution and pharmacokinetic studies indicated that the simvastatin/DMβCD complex exhibited an increased dissolution rate, rapid absorption, and improved bioavailability in rats compared to free drug. Maximum plasma concentration (cmax) and the time to reach it (tmax) were 21.86 μg mL−1 and 1.4 h for the drug complex, 8.25 μg mL−1 and 3.0 h for free drug, respectively. Main pharmacokinetic parameters such as tmax, cmax were significantly different (p < 0.01) between the simvastatin complex and free drug. Bioavailability of the simvastatin complex relative to free drug was up to 167.0 %.